A Research on Cloud Computing and Grid Computing: Some Comparison: Exploring the Similarities and Differences between Cloud Computing and Grid Computing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing is the most recent announced technology that has been launched on the network world. Clouds are considered as a new generation of Grid computing. Clouds consist of data centres which are owned by the same institute. The homogeneity within each data centre in the infrastructure is the main feature for the cloud computing compared to grid computing. This paper provides a definition for the cloud, it discusses many aspects of Cloud Computing, and describes architectures for the cloud (by looking at Amazon’s application (Grep The Web)) and how its cost definition differs from that of Grid computing. This paper focuses on comparing Cloud Computing to previous generations such as Grid Computing, by reviewing some Security and Policy Issues in Cloud and Grid Computing. At the end, this paper describes the similarities and differences between the Grid and Cloud approaches. Two of most well-known computing paradigms are considered throughout this research. These are cluster and cloud computing paradigms. Each of the two paradigms is defined, architecture is considered, areas of applications of each paradigm are explored. Cloud Computing has become another buzzword after Web 2.0. However, there are dozens of different definitions for Cloud Computing and there seems to be no consensus on what a Cloud is. On the other hand, Cloud Computing is not a completely new concept it has intricate connection to the relatively new but thirteen-year established Grid Computing paradigm, and other relevant technologies such as utility computing, cluster computing, and distributed systems in general.